The Impact of Sleep Restriction on Interpersonal Conflict Resolution and the Narcotic Effect - David L. Dickinson; David M. McEvoy; David Bruner (Institute of Labor Economics (IZA), 2021)
Insufficient sleep is commonplace, and understanding how this affects interpersonal conflict holds implications for personal and workplace settings. We experimentally manipulated participant sleep state for a full week prior to administering a stylized bargaining task that models payoff uncertainty at impasse with a final-offer arbitration (FOA) procedure. FOA use in previous trials decreases the likelihood of voluntary settlements going forward—the narcotic effect. We also report a novel result that a significantly stronger narcotic effect is estimated for more sleepy bargaining pairs. One implication is that insufficient sleep predicts increased dependency on alternatives to voluntarily resolution of interpersonal conflict.
Keywords: J52; D74; D90; C92; D83; 330; bargaining; sleep restriction; arbitration; dispute/conflict resolution; narcotic effect